الشخصية المبدعة لدى طلبة معهد الفنون الجميلة وعلاقتها بجنسهم وتخصصهم (Journal Of Educational and Psychological Researches, 2015)
The aims of the research have been determined as:1- Creative personality according to the students of the Fine Arts Institute. • 2- Indication of variances in the creative personality , the manner depending upon the variables of person (males, females). • The research sample consisted of (400) students of Fine Arts Institute for (Boys and Girls)/ Baghdad • The Scientific Research concluded the following:• 1-The students of the Fine Arts Institute have a high from the creative personality . • 2- There is a different in the creative personality according to the                            changeable types (male – female) and there are differences in the statistical function according to the type and specialty.